A history of tax legislation in the Federal Republic of Germany - Matthias Uhl (Philipps-University Marburg, Faculty of Business Administration and Economics, 2013)
This paper presents a historical account of legislated tax changes in the Federal Republic of Germany from 1964 to 2010, thus establishing a database appropriate for the macroeconometric analysis of the fiscal policy transmission mechanism. Ninety-five quantitatively important pieces of tax legislation are identified and characterized along several dimensions: Tax changes are classified as endogenous or exogenous with regard to current macroeconomic conditions, and their revenue impact and timing is reported. The evolution of tax acts is described, capturing changes in tax measures and associated revenue impacts over the whole legislative process. The exposition is also a comprehensive qualitative description of major tax changes and the motivation behind them over the last four decades.
Keywords: E62; H20; K34; N00; 330